Chemistry-based functional proteomics for drug target deconvolution. (June 2012) - Wang, Kui; Yang, Tao; Wu, Qian; Zhao, Xia; Nice, Edouard Collins; Huang, Canhua
Drug target deconvolution, a process that identifies targets to small molecules in complex biological samples, which underlie the biological responses that are observed when a drug is administered, plays an important role in current drug discovery. Despite the fact that genomics and proteomics have provided a flood of information that contributes to the progress of drug target identification and validation, the current approach to drug target deconvolution still poses dilemmas. Chemistry-based functional proteomics, a multidisciplinary strategy, has become the preferred method of choice to deconvolute drug target pools, based on direct interactions between small molecules and their protein targets. This approach has already identified a broad panel of previously undefined enzymes with potential as drug targets and defined targets that can rationalize side effects and toxicity for new drug candidates and existing therapeutics. Herein, the authors discuss both activity-based protein profiling and compound-centric chemical proteomics approaches used in chemistry-based functional proteomics and their applications for the identification and characterization of small molecular targets.